A maleic anhydride grafted cyclic olefin copolymer, its preparation method and use in temporary bonding glue
Patent Information
- Application Number
- CN202611315274.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
现有比如马来酸酐接枝环烯烃共聚物(MAH-g-COC)是用于塑料改性,环烯烃共聚物接枝聚烯烃类弹性体(COC-g-POE)是用于工程塑料,均未涉及临时键合胶的应用场景,无法满足临时键合胶的使用要求
本发明提供的马来酸酐接枝环烯烃共聚物适配临时键合场景,马来酸酐接枝环烯烃共聚物中的酸酐/羧基在键合温度(180-220℃)下与Si-OH的缩合反应加速,形成稳定的酯键界面;解键合后,马来酸酐接枝环烯烃共聚物的溶解性与未改性COC基本一致,仍可使用环己烷/十氢萘等常规溶剂清洗,残胶率<1.0%,与半导体fab现有清洗工艺兼容。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of temporary bonding adhesives, and more particularly to a maleic anhydride-grafted cyclic olefin copolymer, its preparation method, and its application in temporary bonding adhesives. Background Technology
[0002] Cyclic olefin copolymers (COCs) have broad application prospects in the field of semiconductor temporary bonding adhesives due to their precisely tunable Tg, extremely low water absorption, excellent chemical resistance, and high transparency. However, the lack of polar functional groups in the COC molecular chain results in insufficient interfacial adhesion (typically <0.5 MPa) to polar substrates such as silicon wafers / glass, which severely restricts their practical application in temporary bonding.
[0003] Introducing polar functional groups into the COC molecular chain (functionalization modification) is one way to solve its adhesion problem. However, temporary bonding adhesives not only need high adhesive strength, but also need to maintain sufficient adhesive strength at the process temperature (150-200℃), and be removable by conventional solvents after debonding. Existing materials, such as maleic anhydride-grafted cyclic olefin copolymers (MAH-g-COC) used for plastic modification, and cyclic olefin copolymer-grafted polyolefin elastomers (COC-g-POE) used for engineering plastics, do not cover the application scenarios of temporary bonding adhesives and cannot meet the requirements for their use. Summary of the Invention
[0004] The main objective of this invention is to provide a maleic anhydride-grafted cyclic olefin copolymer that meets the requirements for use in temporary bonding adhesives, its preparation method, and its application in temporary bonding adhesives.
[0005] To achieve the above objectives, the present invention provides a maleic anhydride-grafted cyclic olefin copolymer, which is obtained by grafting a cyclic olefin copolymer and maleic anhydride, wherein the maleic anhydride grafting rate of the maleic anhydride-grafted cyclic olefin copolymer is 0.5 to 3.0 wt%.
[0006] This invention utilizes the anhydride groups of maleic anhydride (MAH) to form hydrogen bonds and ester bonds with Si-OH on the silicon wafer surface to enhance interfacial adhesion. The inventors have discovered that a maleic anhydride grafting rate of 0.5–3.0 wt% is a key condition for achieving a balance between adhesion and core performance. Within this grafting rate range, the polar groups introduced by MAH are sufficient to form hydrogen / ester bond anchors at the COC-silicon wafer interface (each MAH molecule provides 2 carboxyl groups), thereby increasing adhesion by 3–8 times. At the same time, the MAH content is sufficiently low to avoid forming a continuous homopolymer phase, keeping the impact on the Tg and transparency of the COC within an acceptable range (Tg decrease <10℃, transmittance >88%).
[0007] When the maleic anhydride grafting rate is too low (<0.5wt%), the introduced polar groups are insufficient to provide effective interfacial anchors, resulting in limited improvement in adhesion. When the grafting rate is too high (>3.0wt%), the formation of MAH homopolymer leads to a decrease in the Tg of COC, a reduction in molecular weight, and a decrease in transparency, resulting in the loss of the core properties required for temporary bonding materials.
[0008] Preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted cyclic olefin copolymer is 0.8 to 2.0 wt%, more preferably 1.0 to 1.5 wt%.
[0009] Preferably, the cyclic olefin copolymer is an addition copolymer of ethylene and norbornene, with a Tg of 100-180℃ and a weight-average molecular weight of 50,000-200,000 g / mol.
[0010] Preferably, the Tg of the maleic anhydride-grafted cyclic olefin copolymer is lower than that of the cyclic olefin copolymer by no more than 10°C, and more preferably by no more than 5°C.
[0011] This invention also faces challenges in the grafting process. Coc (carbon oxide) is prone to thermal degradation (chain scission) at extrusion temperatures, while MAH (maleic anhydride-grafted cyclic olefin copolymer) is prone to homopolymerization at high temperatures, requiring precise control of reaction temperature, residence time, and initiator dosage. How to accurately control the grafting rate of maleic anhydride-grafted cyclic olefin copolymers within the range of 0.5–3.0 wt%, so as to improve adhesive strength while maintaining the core properties of COC, and apply it to the field of temporary bonding adhesives, is also a technical problem that this invention aims to solve.
[0012] To address the problems associated with the grafting process, this invention also provides a method for preparing the above-mentioned maleic anhydride-grafted cyclic olefin copolymer, comprising the following steps: (1) Mix the cyclic olefin copolymer, maleic anhydride, initiator and antioxidant to obtain a raw material mixture; (2) The raw material mixture is added to a twin-screw extruder and melt extruded under nitrogen protection; (3) The extruded product is water-cooled and pelletized, and then vacuum dried to obtain the maleic anhydride grafted cyclic olefin copolymer.
[0013] Preferably, the amounts of each raw material by weight are: 100 parts of cyclic olefin copolymer, 0.5 to 5.0 parts of maleic anhydride, 0.05 to 0.8 parts of initiator, and 0.2 to 1.0 parts of antioxidant.
[0014] Preferably, the initiator is selected from dicumyl peroxide (DCP), benzoyl peroxide (BPO), or 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DBPH); the antioxidant is composed of Irganox 1010 and Irgafos 168, more preferably the mass ratio of Irganox 1010 to Irgafos 168 is 1:1.
[0015] Preferably, in step (1), the mixing process is as follows: maleic anhydride, initiator and antioxidant are dissolved in acetone, then evenly sprayed on the surface of cyclic olefin copolymer particles, and finally the acetone is allowed to evaporate.
[0016] Preferably, in step (2), the extrusion temperature of the melt extrusion is 180–250°C, the screw speed is 60–200 rpm, and the residence time is 1–5 min. More preferably, the extrusion temperature of the melt extrusion is 200–240°C, the screw speed is 80–150 rpm, and the residence time is 2–4 min.
[0017] Preferably, in step (2), the end of the twin-screw extruder is equipped with a vacuum devolatilization section with a vacuum degree of -0.08 to -0.10 MPa. This design is used to remove unreacted MAH and decomposition products, controlling the residual MAH to <0.05 wt%.
[0018] The thermal degradation temperature of COC is approximately 350℃, and it can be safely processed at extrusion temperatures of 200-240℃. The half-life of DCP is 1-3 minutes in this temperature range, which matches the residence time and ensures that the free radical grafting reaction of MAH is fully carried out. The vacuum devolatilization section removes unreacted MAH and low molecular weight byproducts, ensuring the purity and molecular weight of the product.
[0019] The present invention also provides the application of the above-mentioned maleic anhydride-grafted cyclic olefin copolymer in temporary bonding adhesives.
[0020] The present invention also provides a temporary bonding adhesive, comprising, by weight, the following raw materials: 10-50 parts of maleic anhydride-grafted cyclic olefin copolymer, 0-40 parts of cyclic olefin copolymer, 10-25 parts of tackifying resin, 0.3-1.5 parts of antioxidant, and 0.1-0.5 parts of leveling agent.
[0021] Preferably, the content of the maleic anhydride grafted cyclic olefin copolymer in the solid component of the temporary bonded adhesive is 20-80 wt%.
[0022] The beneficial effects of this invention are reflected in: The maleic anhydride-grafted cyclic olefin copolymer provided by this invention is suitable for temporary bonding scenarios. The anhydride / carboxyl groups in the maleic anhydride-grafted cyclic olefin copolymer undergo accelerated condensation reaction with Si-OH at the bonding temperature (180-220℃), forming a stable ester bond interface. After debonding, the solubility of the maleic anhydride-grafted cyclic olefin copolymer is basically the same as that of the unmodified COC, and it can still be cleaned with conventional solvents such as cyclohexane / decahydronaphthalene, with a residual glue rate of <1.0%, which is compatible with the existing cleaning process of semiconductor fabs.
[0023] The method for preparing maleic anhydride-grafted cyclic olefin copolymers provided by this invention achieves precise control of the grafting rate from 0.5 to 3.0 wt% through segmented temperature control, precise initiator dosage control, and vacuum devolatilization design. The process has good repeatability and is suitable for industrial scale-up.
[0024] The maleic anhydride grafted cyclic olefin copolymer of the present invention can be compounded with unmodified COC in any proportion (maleic anhydride grafted cyclic olefin copolymer accounts for 20-80 wt% of solids). The balance between adhesive strength and heat resistance can be adjusted according to specific process requirements, and the formulation is highly flexible. Detailed Implementation
[0025] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.
[0026] Unless otherwise specified, the raw materials, reagents, or apparatus used in the following embodiments can be obtained from conventional commercial sources or by existing known methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods mastered by those skilled in the art. Wherein: Twin-screw extruder with a vacuum devouring section at the end, Nanjing Keya Keyin SHJ series; Cyclic olefin copolymer (COC): TOPAS 6013S (Mw approx. 120,000, Tg 138℃, transmittance ≥91%, room temperature shear strength 0.5 MPa), purchased from TOPAS Advanced Polymers; Maleic anhydride (MAH): analytical grade, purchased from Sinopharm Group; Initiator: Dicumyl peroxide (DCP), chemically pure, purchased from Sinopharm Group; Antioxidant: Irganox 1010 + Irgafos 168 (1:1 by weight), purchased from BASF; Tackifying resin: Eastman Regalite R1100; Organic solvent: cyclohexane + toluene (volume ratio 7:3).
[0027] Example 1 Preparation of maleic anhydride-grafted cyclic olefin copolymers (1) Dissolve maleic anhydride, initiator and antioxidant in acetone, then spray evenly on the surface of cyclic olefin copolymer particles, and finally wait for the acetone to evaporate to obtain raw material mixture; the amount of each raw material by weight is shown in Table 1: Table 1
[0028] (2) The raw material mixture is added to a twin-screw extruder and melt extruded under nitrogen protection; Extrusion temperature: 200℃ / 210℃ / 220℃ / 230℃ (four stages), screw speed 100 rpm, total residence time of four stages 3 min, vacuum degree of vacuum devolatilization stage -0.09 MPa; (3) The extruded product was water-cooled and pelletized, and then vacuum dried at 80°C for 6 hours to obtain the maleic anhydride grafted cyclic olefin copolymer.
[0029] The maleic anhydride-grafted cyclic olefin copolymer prepared in this embodiment has a maleic anhydride grafting rate of 0.52 wt% (determined by chemical titration), a Tg of 135℃ (determined by DSC), and a transmittance of 92.1%.
[0030] Example 2 Preparation of maleic anhydride-grafted cyclic olefin copolymers (1) Dissolve maleic anhydride, initiator and antioxidant in acetone, then spray evenly on the surface of cyclic olefin copolymer particles, and finally wait for the acetone to evaporate to obtain raw material mixture; the amount of each raw material by weight is shown in Table 2: Table 2
[0031] (2) The raw material mixture is added to a twin-screw extruder and melt extruded under nitrogen protection; Extrusion temperature: 200℃ / 215℃ / 225℃ / 235℃ (four stages), screw speed 120 rpm, total residence time of four stages 3 min, vacuum degree of vacuum devolatilization stage -0.09 MPa; (3) The extruded product was water-cooled and pelletized, and then vacuum dried at 80°C for 6 hours to obtain the maleic anhydride grafted cyclic olefin copolymer.
[0032] The maleic anhydride-grafted cyclic olefin copolymer prepared in this embodiment has a maleic anhydride grafting rate of 1.48 wt%, a Tg of 133℃, and a light transmittance of 90.5%.
[0033] Example 3 Preparation of maleic anhydride-grafted cyclic olefin copolymers (1) Dissolve maleic anhydride, initiator and antioxidant in acetone, then spray evenly on the surface of cyclic olefin copolymer particles, and finally wait for the acetone to evaporate to obtain raw material mixture; the amount of each raw material by weight is shown in Table 3: Table 3
[0034] (2) The raw material mixture is added to a twin-screw extruder and melt extruded under nitrogen protection; Extrusion temperature: 210℃ / 220℃ / 230℃ / 240℃ (four stages), screw speed 80 rpm, total residence time of four stages 4 min, vacuum degree of vacuum devolatilization stage -0.08 MPa.
[0035] (3) The extruded product was water-cooled and pelletized, and then vacuum dried at 80°C for 6 hours to obtain the maleic anhydride grafted cyclic olefin copolymer.
[0036] The maleic anhydride-grafted cyclic olefin copolymer prepared in this embodiment has a maleic anhydride grafting rate of 2.95 wt%, a Tg of 128°C, and a light transmittance of 88.2%.
[0037] Comparative Example 1 Preparation of maleic anhydride-grafted cyclic olefin copolymers The preparation method of this comparative example is basically the same as that of Example 2, except that the amount of maleic anhydride is adjusted to 0.2 parts and the amount of DCP is adjusted to 0.02 parts.
[0038] The maleic anhydride grafting rate of this comparative product was 0.18 wt%, the Tg was 137℃, and the transmittance was 92.3%.
[0039] Comparative Example 2 Preparation of maleic anhydride-grafted cyclic olefin copolymers The preparation method of this comparative example is basically the same as that of Example 2, except that the amount of maleic anhydride is adjusted to 8.0 parts and the amount of DCP is adjusted to 1.0 parts.
[0040] The maleic anhydride grafting rate of this comparative product was 4.8 wt%, the Tg was 115℃, the transmittance was 75.3% (obviously yellow), and the Mw decreased to 65,000 (severe degradation).
[0041] Comparative Example 3 Preparation of maleic anhydride-grafted cyclic olefin copolymers The preparation method of this comparative example is basically the same as that of Example 2, except that the four-stage temperature control of the twin-screw extruder is set to 160℃ / 220℃ / 260℃ / 240℃.
[0042] Comparative Example 4 Preparation of maleic anhydride-grafted cyclic olefin copolymers The preparation method of this comparative example is basically the same as that of Example 2, except that the vacuum degree of the devolatilization section is controlled at -0.03MPa.
[0043] Comparative Example 5 Preparation of maleic anhydride-grafted cyclic olefin copolymers The preparation method of this comparative example is basically the same as that of Example 2, except that the total residence time of the material in the twin-screw extruder is 0.5 min.
[0044] Experimental Example 1 Application effect test of temporary bonding adhesive of maleic anhydride grafted cyclic olefin copolymer The maleic anhydride-grafted cyclic olefin copolymers obtained in each example and comparative example were formulated into temporary bonding adhesives, and the formulations are uniformly shown in Table 4: Table 4
[0045] The temporary bonding adhesives prepared from maleic anhydride-grafted cyclic olefin copolymers of each group were subjected to multiple performance tests, and the test results are shown in Table 5. Each performance test item shall be performed according to the following standards: Room temperature lap shear strength: GB / T 7124; Tg: GB / T 19466.2 (DSC method, 10℃ / min, two-stage heating); Light transmittance: GB / T 2410; Residual adhesive content after cleaning: Custom method (decahydronaphthalene, ultrasonic treatment at 40℃ for 5 min, weighing method); Thermal decomposition temperature (Td5%): GB / T 33047 (TGA method, N2 atmosphere, 10℃ / min).
[0046] Table 5
[0047] The results show: (1) Within the grafting rate range of 0.5-3.0%, Example 2 (1.48% grafting rate) achieved a room temperature shear strength of 3.8 MPa, which is 660% higher than that of unmodified COC (0.5 MPa). At the same time, the Tg only decreased by 5℃ (138℃→133℃), the light transmittance remained at 90.5%, and the thermal decomposition temperature was >400℃. The core performance met the requirements for temporary bonding. However, Comparative Example 2, with an excessively high grafting rate (4.8%), although also having a high adhesive strength (3.5 MPa), experienced a significant drop in Tg to 115℃, a light transmittance to 75.3%, and a thermal decomposition temperature to 365℃, resulting in a severe deterioration in core performance.
[0048] (2) After treatment at 200°C, the shear strength of Example 2 was 1.8 MPa, with a retention rate of 47%. This is because the anhydride / carboxyl group of MAH forms a stable ester bond with Si-OH at the bonding temperature, which is not easy to dissociate at high temperature. However, due to severe degradation of COC (Mw decreased from 120,000 to 65,000), the high temperature retention rate of Comparative Example 2 was only 23%.
[0049] (3) Compared with Comparative Example 3, whose temperature in the third segment exceeded the upper limit of 220°C of the present invention, the high temperature caused thermal degradation and cross-linking side reactions of the COC main chain, resulting in abnormally high melt viscosity, decreased selectivity of grafting reaction, severe yellowing caused by thermal oxidation degradation of COC, and a significant decrease in light transmittance. The yellowness index YI of the product of Comparative Example 3 was 12.5 (2.8 in Example 2), and the amount of unreacted MAH residue was 850 ppm (180 ppm in Example 2).
[0050] Compared to Comparative Example 4, where the vacuum level in the vacuum devolatilization section did not meet the conditions of this invention, the grafting rate reached 2.1%, but the unreacted MAH residue was measured at 2100 ppm (compared to 180 ppm in Example 2). The room temperature lap shear strength of the temporary bonding adhesive decreased from 3.8 MPa in Example 2 to 1.8 MPa. Significant residue remained on the silicon wafer surface after debonding, with the residual adhesive rate increasing to 2.3%. This indicates that insufficient vacuum level prevented the effective removal of unreacted MAH monomers and small molecule byproducts. The residual monomers volatilized and generated bubbles in subsequent high-temperature processes, while the acidic residues corroded the silicon wafer surface, severely affecting the bonding-debonding performance of the temporary bonding adhesive and the wafer surface quality.
[0051] Compared to Comparative Example 5, which had a shorter residence time, the room temperature lap shear strength of its temporary bonded adhesive decreased from 3.8 MPa in Example 2 to 1.5 MPa. The tackifier exhibited poor compatibility with the COC matrix, resulting in precipitation, and the residual adhesive rate was 1.2%. It can be seen that the excessively short residence time led to insufficient grafting reaction between MAH and COC, resulting in a low grafting rate and uneven distribution of grafted chains. The tackifier with a low grafting rate could not form an effective interfacial bonding bridge in the COC matrix. Simultaneously, the insufficiently reacted MAH slowly migrated and precipitated during subsequent storage, affecting product stability and performance.
[0052] The key process conditions for achieving high grafting rate, low residue, and high light transmittance are strictly controlled by the four-stage temperature, vacuum degree, and total residence time. Any deviation of any parameter from the scope of this invention will lead to a significant decrease in product performance.
[0053] (4) The solubility of the maleic anhydride grafted cyclic olefin copolymer of the present invention is basically the same as that of the unmodified COC. It can be cleaned and removed by conventional solvents such as decahydronaphthalene (or cyclohexane), with a residual glue rate of <1.0%.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A maleic anhydride-grafted cyclic olefin copolymer, characterized in that, It is obtained by grafting a cyclic olefin copolymer with maleic anhydride, wherein the maleic anhydride grafting rate of the maleic anhydride-grafted cyclic olefin copolymer is 0.5 to 3.0 wt%.
2. The maleic anhydride-grafted cyclic olefin copolymer as described in claim 1, characterized in that, The cyclic olefin copolymer is an addition copolymer of ethylene and norbornene, with a Tg of 100-180℃ and a weight-average molecular weight of 50,000-200,000 g / mol.
3. The maleic anhydride-grafted cyclic olefin copolymer as described in claim 1 or 2, characterized in that, The Tg of the maleic anhydride-grafted cyclic olefin copolymer is lower than that of the cyclic olefin copolymer by no more than 10°C.
4. The method for preparing the maleic anhydride-grafted cyclic olefin copolymer as described in claim 1, 2, or 3, characterized in that, Includes the following steps: (1) Mix the cyclic olefin copolymer, maleic anhydride, initiator and antioxidant to obtain a raw material mixture; (2) The raw material mixture is added to a twin-screw extruder and melt extruded under nitrogen protection; (3) The extruded product is water-cooled and pelletized, and then vacuum dried to obtain the maleic anhydride grafted cyclic olefin copolymer.
5. The method for preparing the maleic anhydride-grafted cyclic olefin copolymer as described in claim 4, characterized in that, The amounts of each raw material by weight are as follows: 100 parts of cyclic olefin copolymer, 0.5 to 5.0 parts of maleic anhydride, 0.05 to 0.8 parts of initiator, and 0.2 to 1.0 parts of antioxidant.
6. The method for preparing the maleic anhydride-grafted cyclic olefin copolymer as described in claim 4 or 5, characterized in that, The initiator is selected from dicumyl peroxide, benzoyl peroxide, or 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; the antioxidant is composed of Irganox 1010 and Irgafos 168.
7. The method for preparing the maleic anhydride-grafted cyclic olefin copolymer as described in claim 4 or 5, characterized in that, In step (2), the end of the twin-screw extruder is equipped with a vacuum devouring section with a vacuum degree of -0.08 to -0.10 MPa.
8. The method for preparing the maleic anhydride-grafted cyclic olefin copolymer as described in claim 4 or 5, characterized in that, In step (2), the extrusion temperature of melt extrusion is 180-250℃, the screw speed is 60-200rpm, and the residence time is 1-5min.
9. The use of the maleic anhydride-grafted cyclic olefin copolymer as described in claim 1, 2 or 3 in temporary bonding adhesives.
10. A temporary bonding adhesive, characterized in that, By weight, it includes the following raw materials: 10-50 parts of maleic anhydride grafted cyclic olefin copolymer, 0-40 parts of cyclic olefin copolymer, 10-25 parts of tackifying resin, 0.3-1.5 parts of antioxidant, and 0.1-0.5 parts of leveling agent.
